Relación entre nivel de escolaridad y falla del método anticonceptivo, en las gestantes del Centro de Salud No 3, Loja - Arias Bermeo, John Paul (2020)
The failure rates of contraceptive methods during their typical use could vary according to the characteristics of the user, also it is due to the difficulty that they experience when using methods that require adherence, such as taking a pill daily, condom use, lack of acceptance of the method due to conflicts such as religious beliefs, customs, sexuality, level of education, etc. In addition to this, the highest percentages of users with low levels of education mark a poor adherence risk group to contraceptive methods that depends on the exclusive attachment of each patient for a higher rate of effectiveness. In the present descriptive, analytical, retrospective research, it was determined the association between the failure of the contraceptive method and the level of education, in 622 pregnant women from the “Health Center No3, Loja”, during the period 2012-2017. It was shown that 13, 3% (n = 83) of the population presented failure of the contraceptive method, the barrier method presented a failure of 7.6%; hormonal contraceptives 3.7%. Furthermore, the failure of the contraceptive method is not related to the level of education, but there is an increased in the risk of contraceptive method failure in the age group between 40 - 49 years. Conclusion: Pregnant women with low educational level are 0.09 more likely to have contraceptive method failure (OR: 0.978; 95% CI, 0.903 - 1.060); but there is a bigger risk of 0.267 in pregnant women in the age range between 40 - 49 years. Keywords: illiteracy, unwanted pregnancy, contraceptive methods, family planning.